Relationship between nutrient intake and iron levels of foremilk and hindmilk in breastfeeding mothers - Dewi Ratnasari; Ani Margawati; Mohammad Zen Rahfiludin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Infants who are not exclusively breastfed are at a risk of iron deficiency. Iron deficiency affects motor development, intelligence, and endurance. Adequate nutrient intake can increase breast milk iron levels, because maternal food intake greatly affects the amount of iron in breast milk. This study aimed to determine the relationship between maternal nutrient intake and iron levels in the breast milk. This study used a cross-sectional approach from October to December 2024. The subjects were 90 mothers who breastfed babies aged 2-24 weeks, with a probability proportional to size. Nutrient intake and breast milk iron stage were the variables that were studied. Data were analyzed using the Pearson’s correlation test and multiple linear regression analysis. Results showed that foremilk iron levels ranged from 60,62 µg/dL to 632,94 µg/dL, while hindmilk iron levels varied from 127,44 µg/dL to 680,38 µg/dL. Iron intake was measured between 13,17 g and 115,6 g, showing a significant correlation between nutrient intake and breast milk (p < 0,05). In addition, it was found that breastfeeding mothers' iron intake was the most influential factor on the breast milk iron stage. In conclusion, maternal iron intake significantly affects breast milk iron levels. Ensuring adequate maternal iron intake, supported by vitamin C consumption, can help increase the availability of iron in breast milk, thereby benefiting infant growth and development.